Counting the cost [videorecording] (Quezon City ABS-CBN News and Public Affairs, 1991)
History of the RP-US bases treaty; Views of the senators on the need to draw up a new bases pact; and A report about the U.S. bases already turned over or about to be turned over to Philippine authorities.
Counting the cost / producer, Veronica Pedrosa (15 min.) -- The Senate : seal of approvaln / producer, Ces Orena Drilon (20 min.) -- The bases for our future / producer, Loren Legarda (20 min.)
VHS.
Keywords: Military bases, American -- Philippines